The Role of National Amil Zakat Agency (BAZNAS) Through Zakat Funds for Poverty Alleviation in Malang Regency - Muhammad Abdul Aziz; Anisah Himatul Ulya; Muhammad Faris Amiruddin (Universitas Darussalam Gontor, 2023)
*English*This research hopefully it can provide benefits, on the distribution zakat funds to poverty alleviation is expected to provide overcome, as well as an understanding of how the benefits of giving zakat assets to people in need, hopefully it will be useful to better understand how the process of managing, distributing and utilizing zakat in order to alleviate people who have poverty and unemployment, because in Islam, poverty and unemployment can damage the faith and social order for society, this research is expected to be for people who are hesitant in providing zakat assistance so that they can become muzakki after understanding the importance of zakat assistance for people in need and help convince zakat institutions in distributing zakat funds to mustahiqs after understanding about it. Documentation in obtaining information, data sources from qualitative research using words, actions, and documents. Qualitative data analysis techniques are performed by data collection, reduction, presentation, and conclusions in qualitative research. Based on the results of the study, BAZNAS in Malang Regency has a role in providing assistance to several aspects of life such as Education, economy, and others, then BAZNAS is reasonably supported by the Government. BAZNAS Malang Regency has several programs conducted to help alleviate poverty that are experiencing shortages in the economy, education, health. These programs include Malang Makmur, Peduli, Sehat, Cerdas and Taqwa, these assistance are consumptive and productive. *Indonesia*Penelitian ini diharapkan dapat memberikan manfaat, dalam penyaluran dana zakat infaq dan shadaqah terhadap pengentasan kemiskinan diharapkan dapat memberikan keringanan dan penanggulanan kemiskinan, serta pemahaman tentang bagaimana manfaat dari pemberian dana zakat terhadap masyarakat yang membutuhkan, proses pengelolaan, pendistribusian dan pendayagunaan zakat agar bisa mengentaskan masyarakat yang mengalami kemiskinan dan pengangguran, karena dalam islam, kemiskinan dapat merusak tatanan keimanan dan sosial masyarakat. penelitian ini diharapkan kepada masyarakat yang ragu dalam memberikan bantuan zakat sehingga mereka dapat menjadi muzakki setelah memahami pentingnya bantuan zakat bagi orang yang membutuhkan, dan membantu meyakinkan mayarakat untuk menyalurkan melalui lembaga zakat dan mendistribusikan dana zakat untuk mustahiq setelah memahami tentang hal itu. Dokumentasi dalam memperoleh informasi, sumber data dari penelitian kualitatif menggunakan kata-kata, tindakan, dan dokumen. Teknik analisis data kualitatif dilakukan dengan pengumpulan data, pengurangan, presentasi, dan kesimpulan dalam penelitian kualitatif. Berdasarkan hasil penelitian, BAZNAS di Kabupaten Malang berperan dalam memberikan bantuan kepada beberapa aspek kehidupan seperti Pendidikan, ekonomi, dan lain-lain, maka BAZNAS didukung oleh Pemerintah. Kabupaten BAZNAS Malang memiliki beberapa program yang dilakukan untuk membantu mengurangi kemiskinan yang mengalami kekurangan dalam ekonomi, pendidikan, kesehatan. Program-program ini termasuk Malang Makmur, Peduli, Sehat, Cerdas dan Taqwa, bantuan ini bersifat konsumtif dan produktif.